Nature explained : a family guide to 20 nature cycles - Brown, Helen, 1994- (Magic Cat Publishing, 2025)
"In Nature Explained, art and science blend together in a fascinating visual tour of more than 20 nature cycles. Discover how trees lose their leaves, what makes flowers bloom, why seeds travel, and many more incredible processes. Split into six sections-trees, leaves, flowers, seeds, mushrooms, and seasons-the book's spreads present different scenes and explain the stories of nature from pollination to photosynthesis, germination to decomposition, in a simple way. Anatomical profiles feature at the start of each section to give a broad overview to each chapter, and feature detailed diagrams and dissections for children to pore over."--